2010 IEEE International Conference on Communications 2010
DOI: 10.1109/icc.2010.5502538
|View full text |Cite
|
Sign up to set email alerts
|

MMSE-Based Partial Crosstalk Cancellation for Upstream VDSL

Abstract: In current DSL systems, crosstalk is a major problem. In the case of in-domain crosstalk and AWGN, it has been shown that the crosstalk can be effectively mitigated using a linear zero-forcing canceler. Furthermore, the complexity can be reduced by only canceling the crosstalk from major crosstalkers on each tone, which is reffered to as partial cancellation. However, such approach does not work e.g. in the case of alien crosstalk. As alien crosstalk is spatially correlated, the zero-forcing canceler performs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…As stated earlier, it requires additional computation of channel matrix inversions. Further, it has been shown in many publications [6,20] that linear receivers (ZF and MMSE) experience significant performance degradation in the presence of alien crosstalk. The SAGE algorithm can effectively mitigate the effect of alien crosstalk as discussed in next section.…”
Section: Self-crosstalk Cancellationmentioning
confidence: 99%
“…As stated earlier, it requires additional computation of channel matrix inversions. Further, it has been shown in many publications [6,20] that linear receivers (ZF and MMSE) experience significant performance degradation in the presence of alien crosstalk. The SAGE algorithm can effectively mitigate the effect of alien crosstalk as discussed in next section.…”
Section: Self-crosstalk Cancellationmentioning
confidence: 99%
“…It is noted that noise is spatially correlated across TPs due to the introduction of crosstalk from an alien source [3]. When the ZF-based receiver [8] is applied after noise whitening, it suffers from a significant performance loss due to the ill-conditioning of the channel after the whitening process as discussed in [11]. Chen et al [10] have shown that a non-linear DFE-ZF can achieve data rate higher than a ZF receiver, though with an increase in computational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study [9], we have shown that the SAGE based iterative receiver can effectively cancel the alien crosstalk to achieve a higher rate (with a little extra complexity). The MMSE based receivers have been proposed in [11,12] as a tradeoff between rate and complexity by eliminating the use of a whitening filter.…”
Section: Introductionmentioning
confidence: 99%
“…The vectored DSL system has been studied in [11][12][13][14][15][16]. In [12][13][14][15][16] simple linear zero-forcing crosstalk cancellation schemes have been proposed that reduce the crosstalk cancellation computational complexity by only removing the dominant crosstalk in the system. This is also referred to as partial crosstalk cancellation (PCC).…”
Section: Introductionmentioning
confidence: 99%
“…Vectored DSL is seen as a very promising technique, and is subject of a standardization procedure of *Correspondence: bli@esat.kuleuven.be 1 Department of Electrical Engineering (ESAT-SCD), Katholieke Universiteit Leuven, Leuven, Belgium Full list of author information is available at the end of the article the international telecommunication union (ITU) [9,10]. The vectored DSL system has been studied in [11][12][13][14][15][16]. In [12][13][14][15][16] simple linear zero-forcing crosstalk cancellation schemes have been proposed that reduce the crosstalk cancellation computational complexity by only removing the dominant crosstalk in the system.…”
Section: Introductionmentioning
confidence: 99%